2011
DOI: 10.1103/physrevb.83.235324
|View full text |Cite
|
Sign up to set email alerts
|

Detection of stacking faults breaking the [110]/[11¯0] symmetry in ferromagnetic semiconductors (Ga,Mn)As and (Ga,Mn)(As,P)

Abstract: We report high resolution x-ray diffraction measurements of (Ga,Mn)As and (Ga,Mn)(As,P) epilayers. We observe a structural anisotropy in the form of stacking faults which are present in the (111) and (111) planes and absent in the (111) and (111) planes. The stacking faults produce no macroscopic strain. They occupy 10 −2 − 10 −1 per cent of the epilayer volume. Full-potential density functional calculations evidence an attraction of MnGa impurities to the stacking faults. We argue that the enhanced Mn density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Among many consequences of such a non-random Mn distribution is the appearance of a local strain, as Mn atoms in the pair are displaced of the GaAs cation positions, whereas the As atom between them is shifted along the [001] direction by as much as 2.6% of the bond length. The resulting strain may contribute to the formation of stacking faults propagating in the (111) and (111) planes [26], observed in (Ga,Mn)As by high resolution electron transmission microscopy [27] and synchrotron xray diffraction [28]. Importantly, according to recent ab initio studies [28], the intersection lines of the stacking fault pairs may enhance further the aggregation of Mn dimers along the [110] crystallographic directions.…”
mentioning
confidence: 99%
“…Among many consequences of such a non-random Mn distribution is the appearance of a local strain, as Mn atoms in the pair are displaced of the GaAs cation positions, whereas the As atom between them is shifted along the [001] direction by as much as 2.6% of the bond length. The resulting strain may contribute to the formation of stacking faults propagating in the (111) and (111) planes [26], observed in (Ga,Mn)As by high resolution electron transmission microscopy [27] and synchrotron xray diffraction [28]. Importantly, according to recent ab initio studies [28], the intersection lines of the stacking fault pairs may enhance further the aggregation of Mn dimers along the [110] crystallographic directions.…”
mentioning
confidence: 99%
“…Recently, Werpachowska and Dietl 22 suggested that the anisotropy mechanism in (Ga,Mn)As films originates from Dzyaloshinsky-Moriya interactions, without assuming any in-plane lattice distortion within their model. Another group of authors have found in the experiment 23 the stacking fault defects in the (111) and (111) planes, which could be responsible for breaking the equivalence of the [110] and [110] directions in the (Ga,Mn)As films. However, to the best of our knowledge, there is so far no experimental evidence nor theoretical description showing that these stacking faults are responsible for the in-plane uniaxial anisotropy.…”
mentioning
confidence: 99%
“…Such behaviour, with the direction being magnetically easier than the perpendicular [110] one, is characteristic of compressively strained (Ga,Mn)As layers with high concentration of valence-band holes 9,21 . The origin of the uniaxial in-plane anisotropy is still debated 2224 and most probably results from the preferred formation of Mn dimmers along the crystallographic direction at the (001) surface during the epitaxial growth of (Ga,Mn)As layers, as concluded from the recent ab initio calculations 25 . The (Ga,Mn)As and (Ga,Mn)(Bi,As) layers are characterized by the T C values of about 105 K and 90 K, respectively, as evaluated from the temperature dependences of SQUID magnetization shown in Fig.…”
Section: Resultsmentioning
confidence: 99%